Association of Immunogenicity and Drug Exposure and the Importance of Target Engagement in ADA Development: A Clinical Case Study of Anti-SARS-CoV-2 Biotherapeutics - Susan C. Irvin; Samit Ganguly; Zhiqiang Wang; Zhongqing Will He; Marguerite Alejandro; Kaitlin Donohue; Chinnasamy Elango; Chris Gallo; Stephen Guttmann; Shawn Kalicharan; Kristina Kameron; James Laird; et al. (The AAPS Journal, 2025)
The administration of therapeutic proteins, such as monoclonal antibodies (mAbs) may result in the formation of anti-drug antibodies (ADA), but there is limited publicly available data for biotherapeutics with exogenous targets or with targets in low abundance systemically. ADAs can impact a biotherapeutic’s safety, efficacy, and pharmacokinetics, so evaluation of immunogenicity is required for all therapeutic proteins. This analysis sought to evaluate the immunogenicity of two mAbs against COVID-19, casirivimab (CAS) and imdevimab (IMD) administered as a cocktail (CAS + IMD), in multiple clinical trials across different participant populations to add knowledge about the immunogenicity risk of protein therapeutics against exogenous targets and the association between immunogenicity and drug exposure. Overall, the incidence of treatment-boosted and treatment-emergent ADAs and neutralizing antibodies in both disease treatment and prophylaxis settings were low (i.e., < 11%). Participants in these studies were followed for up to 225 days post-last dose. Over time, the incidence of treatment-emergent and treatment-boosted immunogenicity for each mAb increased, but the rates and titers remained low overall; when it developed, patients usually developed ADA to both mAbs. Frequency of administration, dose, and route of administration did not appear to impact rates of immunogenicity. Concentrations of CAS and IMD were similar between participants of different immunogenicity status, indicating immunogenicity of CAS and IMD had no impact on pharmacokinetics of these mAbs; there was also no observed impact on safety or efficacy. The data presented here may provide supportive information for assessing the immunogenicity risk of protein therapeutics with exogenous targets. Graphical Abstract